Petrochemical Characteristics of Cenozoic Basalts in Datong, Shanxi - Xiaoqin LI; Xin NIE; Zhuona BAI; Hongfu LIU; Zhiqiang FENG (Taiyuan Ligong Daxue xuebao, 2021)
Basalt in the Cenozoic period in Datong, Shanxi can be divided into two types: alkaline basalt in the northwest and tholeiite basalt in the southeast. Petrological and geochemical analyses were carried out on the basalts in Datong area. As known from the differences between them, the basalt magma in the two regions come from different mantle source regions. Their respective petrology characteristics were summarized. In terms of geochemistry, Mg isotope was used as a chemical tracer to further study the magmatism process in Datong Basin. The results show that the basalt samples in both regions are micro-porphyritic, but the content and proportion of minerals such as feldspar and precious olivine vary greatly; the distribution curves of rare earth elements in the two regions are also significantly different in slope. The relative strength of the magma melting in the two regions was also compared. In addition, the Mg isotope content in Datong area is obviously low, the δ25 Mg value is between -0.36‰~-0.11‰, and the δ26 Mg value is between -0.69‰~-0.21‰, which is lighter than the normal mantle standard. From the geological and geo chemical properties of the basalt after cooling crystallization the geochemical evolution of deep mantle was inferred. The content of Mg isotopic features was used as the main research direction to discuss its genesis and determine the nature of the mantle source region. This research provides reference to understand the cause mechanism, chemical composition, and other factors of Cenozoic basalts in north China.